DARI AIR PANAS KE AIR HIDUP: ANALISIS TEOLOGIS KOMPARATIF 'PADAKANAN' DESA TORAGET DENGAN PERIKOP YOHANES 4:1-42 - Mumu, Andre Shevcenco; Supit, Elma Gabriela (DELAHA: Journal of Theological Sciences, 2025)
In Toraget Village, Minahasa, the ‘Padakanan’ hot springs serve as a vital center for communal life, yet its potential theological meaning remains unexplored. A gap exists between the communal physical practice around the hot springs and its theological interpretation as "Living Water". This research aims to bridge this gap by constructing a contextual theology through a comparative-thematic analysis of the practices at ‘Padakanan’ and the narrative of Jesus's encounter with the Samaritan woman (John 4:1-14). Using a qualitative method with a contextual theology approach, this study collected data through observation, interviews, and biblical exegesis. The analysis found four main points of convergence: (1) The water at ‘Padakanan’ as a gift of creation becomes a metaphor for "Living Water" as the gift of salvation. The space of ‘Padakanan’ as a communal hub reflects the potential for a transformative space of encounter that transcends social boundaries; (2) The physical purification process at ‘Padakanan’ symbolizes the spiritual purification process from sin towards restoration in Christ. (3) The vital role of women as community agents at ‘Padakanan’ is theologically affirmed by the Samaritan woman's role as a gospel evangelist. This study concludes that ‘Padakanan’ can be interpreted as a "natural sacrament" that offers pastoral and missiological implications for the church to develop a ministry rooted in the local cultural context.